The Perception of Congregants Towards the Tafsir Al-Ibriz Study (Living Qur’an Study at Majelis Ta’lim Masjid Sabilun Najah) - Fahma Nafillah; Alfet Robi' Nur Muhammad (International Journal of Research, 2024)
This study discusses the response of the congregants towards the existence of a majelis ta'lim (Islamic study group). In this majelis ta'lim, there is a study of tafsir al-Ibriz, which not only explains the interpretation of the Qur'an but also includes discussions about everyday life. The focus of this research is to examine the congregants' perceptions of the tafsir al-Ibriz study, the factors influencing their participation in this study, and how the study is implemented in the majelis ta'lim at Masjid Sabilun Najah. This is a qualitative study using descriptive qualitative research methods. The sources of data include Ustadz Ainur Rofiq, the teacher at the Sabilun Najah majelis ta'lim, and several congregants who attend the tafsir al-Ibriz study. Data collection methods include interviews with the teacher and some congregants, observations during the implementation of the tafsir al-Ibriz study, and documentation for supporting records. The findings of this study indicate that the congregants' response to the existence of this study is very positive. The congregants expressed positivity because they wish to deepen their religious knowledge and strengthen their faith. The factors influencing their participation in the study include the desire to increase their religious knowledge, improve themselves, and seek rewards for their life in both this world and the hereafter.